Special Issue on Using Econometrics for Assessing Economic Models: An Introduction - Katarina Jusélius (Economics: The Open-Access, Open-Assessment E-Journal, 2009)
Two methodological approaches to empirical economics which are labelled 'theory first' versus 'reality first' are introduced building the background for the discussion of the individual contributions to this special issue.
Keywords: B4; C3; 330; CVAR; pre-eminence of theory; general-to-specific; empirical macroeconomic methodology; VAR-Modell; Methodenkritik; Wirtschaftsforschung; Theorie